Early Childhood Education - Farland-Smith, Donna (IntechOpen, 2019)
This book will serve as a resource for students, researchers, and practitioners in the area of early childhood education. The 18 chapters are divided and organized into the major areas relevant to early childhood education: early childhood development, play, science, mathematics, technology, literacy, and exceptional learners. Each chapter contains an overview of background information pertinent to the chapter and a synopsis of research or a new research study. The information contained in this book provides a foundation for past and/or present research and suggests future research studies.